Educational Institutions and Climate Change Awareness: "Analytical Study of UNESCO's Document on Climate Action" - Abdelfatah Zahra (Port Said Journal of Educational Research)
The current research aimed to identify the role of the educational institution in achieving climate change awareness as stated in UNESCO's document on climate action, by highlighting the school's comprehensive approach to addressing the phenomenon of climate change, in addition to upgrading the essential mechanisms for this. The descriptive approach was used for analyzing UNESCO's document on climate action and activating the content analysis style in its qualitative dimension. The research found that awareness of the phenomenon of climate change is one of the most important strategies that enable individuals to prepare to face this phenomenon and try to mitigate its effects on societies. Educational institutions have the largest role in achieving awareness of climate change, which enriches environmental knowledge and skills of rational dealing with the environment.